Pembentukan Varietas Jagung Komposit Kaya Vitamin Provit A1 dan Provit A2 - M. Yasin H.G.; Syahrir Mas'ud; Faesal Faesal (Iptek Tanaman Pangan, 2012)
Open pollinated varieties could be developed through intra and inter population improvement. High yielding variety could be obtained by repetitive cycles of selection to generate families, to be evaluated and to be recombined. Provit-A maize variety has a high vitamin-A (beta-Carotene), up to 8-15 µg/g where normal maize contains 1.0 µg/g. Provit-A maize was developed from population Obatanpa(Pro-A)BC1C2-F2 and KUI Carotenoid Syn, which contains beta-carotene 4.1 and 8.0 µg/g, compared to normal maize variety Sukmaraga and Srikandi Kuning-1 of only 2.40 and 1.90 µg/g. Yield potential of Provit A variety is 6.0-7.0 t/ha, 17.1-22.0% more compared to normal maize. Beta carotene is recommended to overcome blindness in child age. Provit-A variety is recommended to be grown in the eastern part of Indonesia to be used as foods supplement or subtituting wheat. Isolated farm is needed to produce seed as well as for the location of training for farmers and extention workers.